Sacrifices among the Slavs: Between Archeological Evidence and 19th Century Folklore - Wenska, Izabella (Fundacja Rzeszowskiego Ośrodka Archeologicznego, 2015)
This article discusses the subject of sacrifices among the Slavs using textual, archeological and ethnographic evidence. Although it is a well-known fact that there are not many textual sources concerning early medieval Slavic culture and religion, some aspects of their customs and rituals can be reconstructed by referring to folkloristic materials. According to many scholars, Slavic folk culture (especially that of Eastern Slavs) has preserved some traces of pre-Christian practices, but it is important to maintain a careful approach to ethnographic sources and avoid far-reaching interpretations of archeological evidence in their light. In spite of methodological difficulties, by critically combining different categories of sources it seems possible to offer new interpretations of Slavic beliefs.
Ofiary u Słowian: pomiędzy znaleziskami archeologicznymi a dziewiętnastowiecznym folklorem
Keywords: sacrifices; Slavic rituals; Slavic folklore; ethnographic sources; folk beliefs